Kebebasan akademis pada masa Khalifah Al-Ma’mun dan relevansinya dengan konsep merdeka belajar di Indonesia - Hasibuan, Nur Syakinah; Arsyad, Junaidi; Salminawati (Tawazun: Jurnal Pendidikan Islam, 2023)
This research aims to determine academic freedom during the time of Caliph Al-Ma'mun and its relevance to the concept of freedom to learn in Indonesia. The method used in this research is using qualitative research methods with a library research approach and using historical approach steps. The focus of analysis in this research is to examine the social and intellectual conditions during the Abbasid era, especially during the time of the caliph Al-Ma'mun, so that several academic freedom practices were discovered that occurred at that time. The results of this research show that there is significant relevance between academic freedom during the time of Caliph Al-Ma'mun and the concept of independent learning which is being launched by the Indonesian Minister of Education and Culture in overcoming the low interest in literacy and numeracy among Indonesian children after the Covid-19 pandemic. The concept of Independent Learning is intended to give students the freedom to learn according to their interests and talents as an effort to grow a generation that will bring changes in competence in their respective fields. These include similarities in aspects of the definition of freedom itself, the assimilation factor as a driving force for the development of knowledge, similarities in the implementation of outdoor learning, namely during the time of the Caliph Al-Ma'mun it was called a scientific spirit, while in independence learning was called an outing class, similarities in development methods science, namely the debate/jaldah method with the discussion method, similarities in efforts to develop science through research activities and writing down the work of the research. As well as mastery of foreign languages in translation activities during the time of Caliph Al-Ma'mun by strengthening foreign languages, especially English, in independent learning. Abstrak Penelitian ini bertujuan untuk mengetahui kebebasan akademis pada masa khalifah Al-Ma`mun dan relevansinya dengan konsep merdeka belajar di Indonesia. Adapun metode yang digunakan dalam penelitian ini adalah menggunakan metode penelitian kualitatif dengan pendekatan pustaka (library research) serta menggunakan langkah-langkah pendekatan sejarah. Fokus analisis dalam penelitian ini adalah mengkaji kondisi sosial intelektual pada masa Bani Abbasiyah khususnya pada masa khalifah Al-Ma`mun sehingga ditemukan beberapa praktik kebebasan akademis yang terjadi pada masa itu. Hasil penelitian ini menunjukkan bahwa terdapat relevansi yang signifikan antara kebebasan akademis pada masa khalifah Al-Ma`mun dan konsep merdeka belajar yang sedang dicanangkan oleh Menteri Pendidikan dan Kebudayaan Indonesia dalam mengatasi rendahnya minat literasi dan numerasi anak-anak Indonesia pasca Pandemi Covid-19. Konsep Merdeka belajar dimaksudkan untuk memberikan kebebasan kepada peserta didik untuk belajar sesuai minat dan bakatnya sebagai upaya untuk menumbuhkan generasi yang akan membawa perubahan pada kompetensi dalam bidang masing-masing. Di antaranya kesamaan dalam aspek definisi kebebasan itu sendiri, faktor asimilasi sebagai pendorong berkembangnya ilmu pengetahuan kemiripan dalam pelaksanaan pembelajaran di luar ruangan yaitu pada masa khalifah Al-Ma`mun disebut dengan rihlah ilmiah sedangkan dalam merdeka belajar disebut dengan outing class, kesamaan dalam metode pengembangan ilmu pengetahuan yaitu metode debat/jaldah dengan metode diskusi, kesamaan dalam upaya pengembangan ilmu pengetahuan melalui kegiatan penelitian/riset serta menuliskan karya dari penelitian tersebut. Serta penguasaan bahasa asing dalam kegiatan penerjemahan pada masa Khalifah Al-Ma`mun dengan penguatan bahasa asing khususnya bahasa Inggris dalam merdeka belajar.